VAS KOPI (VAS KOREK API) AS A CREATIVE AND INNOVATIVE EFFORT FOR STKIP SINGKAWANG STUDENTS - Nindy Citroresmi P; Ayu Susantri; Sri Septiani; Yeni Yeni; Rinko Oi (STKIP Singkawang, 2020)
The entrepreneurship program entitled VAS KOPI (Vase of Matches) As a Creative and Innovative Effort for STKIP Singkawang Students aims to develop student interest and creativity in opening business opportunities that can add experience, motivate in developing innovations and creations. One of them is by using matches.